Asset mapping and Whanau action research: 'New' subjects negotiating the politics of knowledge in Te Rarawa - Underhill-Sem, Yvonne; Lewis, Nick (Asia Pacific viewpoint, 2008)
Te Runanga o Te Rarawa is the tribal council representing the interests of the marae (tribal commons) and hapu (a subtribal kin group) that make up the iwi (a Maori tribe) of Te Rarawa in the far north of Aotearoa/New Zealand. In April 2005, officials approached us to help them secure a valuable funding stream tagged to marshalling resources for material development in the area. They sought curriculum vitae and assistance in reframing the funding specifications. Intrigued, armed with a conceptual toolkit drawn from Gibson‐Graham's ideas of post‐development and asset‐based community mapping, and confident that we could add value, we agreed to help. This paper examines the complex politics of our involvement and our changing positioning as researcher subjects. We argue that negotiating a politics of knowledge for projects of this nature requires engagement in complex representational politics of place and divisive identity politics that rage around it. There are no easy protocols for outside researchers, but with appropriate humility and sensitivity to these politics, we can rely on, and should stand up for, the value of our work, which lies in commitments to excellence in scholarship. We cannot and should not seek to control these politics, which will chew us up and spit us out – humanely and with good grace or otherwise. However, good academic work will recognise and adapt to them. In our particular case, we argue that our work had significant value; and in this paper, we trace the production of this value.